Muslims in Papua New Guinea : major problems and challenges since 1977 - Abiola, Ibraheem Mikail (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This research is an introduction to the historical investigation into the problems and challenges of Muslims in Papua New Guinea. After almost 40 years of Islamic existence in Papua New Guinea. Muslims constitute about 1% of the population of the country. In understanding the situation facing Muslims in Papua New Guinea, some factors that contributed to the growth and spread of Islam were assessed, most especially the existence of foreign Islamic bodies such as World Assembly of Muslim Youth (WAMY) and RegionalIslamic Da'wah Council of Southeast Asia and Pacific (RISEAP). More importantly, this researchanalyses major problems and challenges facing the Muslims which include Christian missionaries, media houses and the policies of the government of Papua New Guinea toward Muslims. The attitude of Christian missionaries to Muslims is also identified in this research. Suggestions pertaining to the future prospect of Muslims in Papua New Guinea were also provided.